2017
DOI: 10.1080/08856257.2017.1412640
|View full text |Cite
|
Sign up to set email alerts
|

The effects of educational computer game on low-performing children’s early numeracy skills – an intervention study in a preschool setting

Abstract: The aim of this study was to determine the effects of an educational computer game, Lola's World, on low-performing children's early numeracy skills. Four preschools with 33 children from families of low socioeconomic status (Mage = 5.5 years) took part in this study. Of the 33 children, 23 were split randomly into two groups: an intervention group playing a numeracy game (Lola's World) and an active control group playing an early reading skills game (Lola's ABC party). The remaining 10 children served as a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
0
14
0
4
Order By: Relevance
“…However, several scholars have stressed the possibilities of ET to also enhance motivational outcomes and efficiency outcomes in learners [27,101]. Although some studies qualitatively reported children's engagement and motivation during ET use [40,43,65],…”
Section: Limitationsmentioning
confidence: 99%
“…However, several scholars have stressed the possibilities of ET to also enhance motivational outcomes and efficiency outcomes in learners [27,101]. Although some studies qualitatively reported children's engagement and motivation during ET use [40,43,65],…”
Section: Limitationsmentioning
confidence: 99%
“…In previous studies, only Räsänen and colleagues (2009) and Salminen and colleagues (2015) conducted their studies in authentic (pre)school settings as we did. When intervention studies are conducted in children's daily environments, it is challenging to control for distracting factors and get good intervention effects (Aunio and Mononen 2018).…”
Section: Discussionmentioning
confidence: 99%
“…CAI in mathematics for children in the early grades mainly focuses on basic numerical skills. To the best of our knowledge, the existing mathematics programmes and games that have been used in research-based CAIs for low-performing children in kindergarten and the early grades include Calcularis (Käser et al 2013), GraphoGame Math (Salminen et al 2015), Lola's World (Aunio and Mononen 2018), and The Number Race (NR; Wilson et al 2006b;Wilson et al 2009;Räsänen et al 2009;Salminen et al 2015), which is used in this study.…”
Section: Computer-assisted Intervention (Cai)mentioning
confidence: 99%
“…In Aunio and Mononen [3] two control groups were included. One control group is passive, whereas the other control group is an active control group trained in a topic other than math (i.e.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%